Students’ Perceptions of Environment-Based Biology Learning in the School Surroundings among Students at SMA Swasta HAS Sepakat Negeri Lama, Labuhanbatu - Nasution, Rani Rahmadani; Hasibuan, Rosmidah; Harahap, Risma Delima (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze students’ perceptions of biology learning based on the school surrounding environment at HAS Sepakat Negeri Lama Private Senior High School, Labuhanbatu. This study employed a quantitative approach with a descriptive survey design. The participants were 60 Grade X students from two classes, selected using total sampling. Data were collected using a closed-ended questionnaire consisting of 15 items covering cognitive, affective, and conative dimensions. The data were analyzed using descriptive statistics and the Mann–Whitney U test. The results showed that students’ perception scores ranged from 3.63 to 4.28, falling within the high to very high categories. These findings indicate that students perceived environment-based biology learning as beneficial, relevant, and engaging. The Mann–Whitney U test showed no significant difference in students’ perceptions between the two classes (p = 0.382), suggesting relatively similar learning experiences across groups. Overall, environment-based biology learning can support contextual and meaningful learning by connecting biological concepts with real environmental phenomena. These findings provide practical implications for biology teachers in designing learning strategies that utilize the surrounding environment as an authentic learning resource and contribute to the development of contextual learning in biology education.